THE USE OF DIGITAL EDUCATIONAL TOOLS IN TEACHING RUSSIAN AS A FOREIGN LANGUAGE IN HIGHER EDUCATION (Educator Insights: Journal of Teaching Theory and Practice, 2026)
The integration of digital educational tools into higher education has significantly transformed the teaching of Russian as a foreign language. This article examines the role of digital platforms and technologies in improving language instruction for university students. Using a qualitative descriptive approach and classroom-based examples, the paper explores how online tools support vocabulary development, grammar practice, speaking activities, feedback, and student engagement. The study highlights both the advantages and limitations of digital instruction, particularly in multilingual learning environments. The findings suggest that digital tools are most effective when they are used not as a replacement for teaching, but as a structured extension of communicative, interactive, and student-centered learning in Russian language education.